Analysis of Corruption Crimes In the Islamic Perspective - syamsul bachri (Faculty of Law, Universitas Pekalongan, 2025)
This study analyzes the effectiveness of criminalizing corruption in an effort to restore state financial losses. Corruption not only damages the integrity of the government system but also causes huge losses to the country's finances which negativelyimpacts economic and social development. This study examines criminal law policies in Indonesia related tocorruption, including the application of criminal sanctions in the form of imprisonment, fines, and assetconfiscation as an effort to recover state losses. The method used in this study is a literature study andjuridical analysis of anti-corruption laws, especially Law No. 31 of 1999 jo. Law No. 20 of 2001. In addition,this study highlights the importance of harmonization of national law with international law to make it easierto track corruption assets abroad and the need to increase the capacity of law enforcement officials sothat criminal justice runs effectively. With the results of the return of state losses in corruption crimes inIndonesia, it is comprehensively regulated to ensure that the state recovers some or all of the financiallosses incurred. Sanctions in the form of fines, return of losses, and confiscation of assets are the maininstruments applied. In addition, cross-agency cooperation and international coordination also playan important role in supporting the optimization of loss rest. The capacity of law enforcement officialsneeds to be improved, including training in asset tracking and handling of complex cases to make thelegal process run professionally